Reengineering the 2010 Census: Risks and Challenges - National Research Council (U.S.). Panel on Research on Future Census Methods; Cork, Daniel L.; Cohen, Michael L.; King, Benjamin F.; National Research Council (U.S.). Committee on National Statistics (National Academies Press, 2004)
At the request of the U.S. Census Bureau, the National Research Council's Committee on National Statistics established the Panel on Research on Future Census Methods to review the early planning process for the 2010 census. This new report documents the panel's strong support for the major aims of the Census Bureau's emerging plan for 2010. At the same time, it notes the considerable challenges that must be overcome if the bureau's innovations are to be successful. The panel agrees with the Census Bureau that implementation of the American Community Survey and, with it, the separation of the long form from the census process are excellent concepts. Moreover, it concurs that the critically important Master Address File and TIGER geographic systems are in dire need of comprehensive updating and that new technologies have the potential to improve the accuracy of the count. The report identifies the risks and rewards of these and other components of the Census Bureau's plan. The report emphasizes the need for the bureau to link its research and evaluation efforts much more closely to operational planning and the importance of funding for a comprehensive and rigorous testing program before 2010.